2012
DOI: 10.1155/2012/392050
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Factors from Bone Marrow Stromal Cells Upregulate IL-10 and Reverse Acute Kidney Injury

Abstract: Acute kidney injury is a devastating syndrome that afflicts over 2,000,000 people in the US per year, with an associated mortality of greater than 70% in severe cases. Unfortunately, standard-of-care treatments are not sufficient for modifying the course of disease. Many groups have explored the use of bone marrow stromal cells (BMSCs) for the treatment of AKI because BMSCs have been shown to possess unique anti-inflammatory, cytoprotective, and regenerative properties in vitro and in vivo. It is yet unresolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…In an effort to understand whether MSCs are acting from within the kidney or from distant organs, we surveyed human cytokine/growth factor levels in the kidney and serum. Previous studies showed that IL‐10 produced by MSCs improves AKI . We show that more IL‐10 from human MSCs was present in the kidney after enhanced homing with pFUS+MSCs compared to MSCs alone, suggesting that enhanced MSC homing to kidneys plays a role in improved outcomes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In an effort to understand whether MSCs are acting from within the kidney or from distant organs, we surveyed human cytokine/growth factor levels in the kidney and serum. Previous studies showed that IL‐10 produced by MSCs improves AKI . We show that more IL‐10 from human MSCs was present in the kidney after enhanced homing with pFUS+MSCs compared to MSCs alone, suggesting that enhanced MSC homing to kidneys plays a role in improved outcomes.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown MSCs do not integrate into tissue, but rather act via paracrine effects to improve AKI by acting upon multiple pathophysiological pathways both locally and systemically . MSCs located in the glomeruli and peritubular spaces can interact with tubular and immune cells through paracrine signaling, and possibly transfer of mRNA, to exert effects including stimulation of kidney regeneration, and downregulation of inflammation and apoptosis . These infused cells can secrete factors such as VEGF, FGF, IL6, TGF‐β, MCP‐1, IGF‐1, and SDF‐1α that have been shown to improve AKI .…”
Section: Discussionmentioning
confidence: 99%
“…Each of these targets is inducible in response to 1,25D in both animals and humans, [136][137][138][139][140][141][142][143][144][145][146][147][148] and plays an important role in the pathogenesis of AKI. [149][150][151][152][153][154][155][156] In addition to strong data from preclinical studies, the relevance of decreased circulating vitamin D metabolite levels in human AKI is supported further by epidemiologic studies in critically ill patients. These studies consistently have found that lower levels of 25D associate independently with an increased risk of acute organ injury and death.…”
Section: Vitamin D Metabolites As Novel Therapies In Aki and Criticalmentioning
confidence: 99%
“…Bone marrow‐derived mesenchymal stem cells (BMSCs) are always served as reserves for bone tissue regeneration widely due to their self‐renewal ability and multiple differentiation potential, especially osteogenic potential . Besides, BMSCs have been revealed as the regulator of angiogenesis and inflammatory through secreting varies of growth factors or cytokines. Thus, BMSCs are always considered as a source of osteoblast progenitor and play an important role in bone regeneration and remodelling collaborating with functionalized scaffolds.…”
Section: Introductionmentioning
confidence: 99%